Developing an outward mindset model for primary school administrators in Northeastern Thailand - Phanjamrat, Theerawan; Sirisooksilp, Saowanee; Thaksino, Prakrittiya (Edelweiss Applied Science and Technology, 2025)
This research aimed to: (1) study the components and indicators of the Outward Mindset of primary school administrators in the Northeastern region; (2) examine the consistency of the component model and indicators of the Outward Mindset of primary school administrators in the Northeastern region with empirical data; and (3) create and evaluate the Outward Mindset development model for primary school administrators in the Northeastern region. The study consisted of three phases: Phase 1 studied the components and indicators of the Outward Mindset of primary school administrators; Phase 2 examined the consistency of the component model and indicators of the Outward Mindset of primary school administrators in the Northeastern region; and Phase 3 involved the creation and evaluation of the Outward Mindset development model for primary school administrators in the Northeastern region. The study results indicated that: 1) from the qualitative study, there were four components and twelve indicators; 2) from the component analysis, the indicators could be grouped into four components, and from the confirmatory factor analysis, it was found that the developed model of components and indicators of the Outward Mindset of primary school administrators in the Northeast region was consistent with empirical data; and 3) the Outward Mindset Development Model for Primary School Administrators in the Northeastern Region was established.